Flexural performance of concrete composite metal decking with different base-metal-thickness new smart system - Yip, Chun-Chieh; Wong, Jing-Ying; Amran, Mugahed; Rashid, Raizal S.M.; Nehdi, Moncef L. (Elsevier BV, 2023)
Industrial Revolution 4.0 has led to the age of automation and industrialized building systems. Composite slabs gain its popularity in the modern construction industry due to its speed of construction and cost saving features with lightweight structure. However, from time to time the manufacturer will introduce new corrugated roll forming cold formed steel metal decking systems, which cause the end user to ponder if the product is up to desired performances. The aim of this research is to study the structural performance of SMARTDEK composite slab composed of 0.75 mm and 1.0 mm thickness compared to the conventional reinforced concrete slab under flexural strength, deflection, and failure mode. Concrete slab with thickness of 130 mm was constructed to uncover the ultimate load capacity of the slabs. The novelty of this research is the discovery of longitudinal shear resistance constant through derived equations and the new SMARTDEK profiled composite slab performs better than the conventional slab. Four-point flexural tests were conducted according to ASTM C293 standards to determine the performance of the slabs, and three linear variable displacement transducers (LVDTs) were used to determine the deflection of the slabs. Load-Deflection graphs were plotted for the specimens to determine the yielding point and ultimate point of the slabs. The composite slab with 1.0 mm Base-Metal-Thickness (BMT) had the highest ultimate strength at 75 kN, followed by the composite slab with 0.75 mm BMT at 65 kN, and finally the conventional slab at 39 kN. The failure mode of the conventional slab was pure flexural; while the composite slab first failed in flexural, followed by longitudinal slip failure due to flexural and flexural-shear cracks, which disabled the composite action between the concrete slab and metal decking. The finding showed that the increasing thickness of the metal decking improves the slab strength which results in higher ultimate strength and reduces the overall deflection of the slab. Moreover, the breakthrough of this research is that increasing the overall thickness of the slabs increases the performance in loading’s capacity which could result in higher ultimate strength.